Perbandingan Produksi Tangkapan dan Pendapatan Nelayan Nike di Teluk Gorontalo Menggunakan Alat Tangkap Tagahu dan Totalu’o - Rahim, Fadhilah Apriliyani; Yusuf, Mohamad Iqbal; Nusi, Ibrahim A.; Pasisingi, Nuralim; Habibie, Sitty Ainsyah (Fakultas Kelautan dan Teknologi Perikanan - Universitas Negeri Gorontalo, 2025)
This study aimed to compare the production of nike in Gorontalo Bay using Tagahu and Totalu'o fishing gear. This research was conducted during 2 months of the fishing season, June and July. Data collection included observation and interviews using structured questionnaires with nike fishermen in Gorontalo Bay, Tomini Bay. The study results revealed that the total catches per fishing season by fishermen using Tagahu in June was 1,683 kg and in July it reached 1,360 kg, while the catch using Totalu'o was much less, only 433 kg in June and 380 kg in July. The fishermen total income in June who operated Tagahu was IDR 636,562 to IDR 1,117,812 per trip, while for fishermen operated Totalu'o fishing gear it ranged from IDR 1,305,375 to IDR 1,764,750 per trip. Meanwhile, the total income per trip by the fishermen in July who functioned Tagahu was IDR 537,857 to IDR 1,178,125. While for fishermen of Totalu'o fishing gear it was IDR 1,692,750 to IDR 2,343,375.